ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP TINGKAT KEPUASAN NASABAH TABUNGAN SIMPEDES PADA PT BANK RAKYAT INDONESIA (PERSERO), TBK KANTOR CABANG PATTIMURA SEMARANG - Shelvia Amelinda Nurmaulia; Aris Sunindyo (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2019)
The purpose of research is to analyze the service quality influence to the customer satisfaction of Simpedes savings product in Bank Rakyat Indonesia ltd Pattimura Branches Semarang. This research is quantitative causal applied research. The population in this research is Simpedes savings product in in Bank Rakyat Indonesia ltd Pattimura Branches Semarang as many as 100 customers. Data collection method used the purposive sampling. The data used in the research are primary and secondary data. The analytical model used in this research is Multiple Linear Regression. Based on the results of research, service quality has significantly influence on the customer satisfaction. Emphaty has the greatest influence customer satisfaction with beta of 31,1 and the lowest influence customer satisfaction is reliability with beta of 11,8.